16 Comparison of Prevalence of Polycythemia between Nasal Testosterone Gel vs Intramuscular Testosterone Cypionate: Evaluation of Data from an Ongoing Phase IV, Open-Label, Randomized Clinical Trial. Issue 1 (1st April 2022) - Diaz, P; Gonzalez, DC; Ory, J; Balaji, NC; Reddy, R; Molina, M; Ramasamy, R
ABSTRACT: Introduction: Men taking testosterone therapy (TT) have potential side effects such as polycythemia, testicular atrophy, and decreased spermatogenesis. Recent evidence has shown that the modality of delivery may affect the prevalence of these side effects. We hypothesized that intranasal short-acting testosterone will have a lower rate of polycythemia than injectable long-acting testosterone because shorter-acting formulations can more closely mimic normal physiology. Objective: To compare the effects of Natesto and Testosterone Cypionate (TC) on hematocrit and serum testosterone levels in testosterone deficient men over 4 months. Methods: This Phase IV, randomized, open-label clinical trial was performed on 30 symptomatic, testosterone deficient men with at least two serum testosterone levels below 300 ng/dL drawn before 10AM. Men were randomized (1:1) to receive either Natesto three times per day (5.5mg per nostril) and intramuscular TC (200mg) once every two weeks. Hematocrit and serum testosterone were evaluated before and after four months. The primary outcome was changes in hematocrit. Secondary outcomes were changes in E, DHT, PSA and 17-OHP. Data analysis was performed using two-sample and single-sample T tests, and determination of equal or unequal variances was computed using F tests. Results: The median participant age was 45 years old. At baseline, serum T of all participants was 239.6 ng/dL and hematocrit of 43.1. Prevalence of participants who screened positive for OSA on STOP-BANG questionnaire for Natesto and TC group were 75% and 78%, respectively. The 4-month change in hematocrit in the Natesto group (-1.1 from baseline) was significantly less than the change in hematocrit seen in the TC group (+5.1 from baseline), (p < 0.001, t = -7.6). Prevalence of polycythemia (HCT > 52%) after 4 months was 0% in Natesto group and 5.5% in TC. Both groups increased testosterone levels above baseline at 1 and 4 months, with a larger increase seen in the TC group compared to Natesto (p = 0.029, t = 1.71), (Figure 1B). In the Natesto group, secondary outcomes E, DHT, PSA, and 17-OHP changed -2.9 (p = 0.54), +4.3 (p = 0.64), +0.34 (p = 0.52), and +1.6 (p = 0.88) from baseline, respectively (Figure 1C). In the TC group, secondary outcomes E, DHT, PSA, and 17-OHP changed +21.2 (p= 0.019), +4.3 (p = 0.64), -0.34 (p = 0.52), and -42.9 (p > 0.001) from baseline, respectively (Figure 1C). Conclusions: Short-acting nasal testosterone does not appear to increase serum hematocrit when compared to intramuscular testosterone cypionate, while both modalities returned men to a eugonadal serum testosterone level (>300 ng/dL) in 83% of men. In men who are at risk of developing polycythemia (obstructive sleep apnea, high baseline hematocrit), nasal testosterone gel or other short acting formulations should be strongly considered. Disclosure: Yes, this is sponsored by industry/sponsor: Acerus Pharmaceuticals Clarification: Industry funding only - investigator initiated and executed study